2002
DOI: 10.1152/japplphysiol.00622.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral contraceptives on peak exercise capacity

Abstract: .-We examined the effects of menstrual cycle phase and oral contraceptive (OC) use on peak oxygen consumption (V O2 peak). Six moderately active, eumenorrheic women (25.5 Ϯ 1.5 yr) were studied before and after 4 mo of OC. Subjects were tested during the follicular and luteal phases before OC and the inactive and high-dose phases after OC. Before OC, there were no significant differences between the follicular and luteal phases in any of the variables studied. There were also no differences between the inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
4
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 23 publications
7
78
4
2
Order By: Relevance
“…Aerobic performance as measured by VO2max has been shown to reduce by 5 -15% in trained and active women using a triphasic OCP [95,96], however, research remains equivocal when considering the monophasic pill [72]. Anaerobic performance, high-intensity intermittent performance and strength appear to be largely unaffected by OCP, however, more well-controlled studies are required [72,93].…”
Section: 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Aerobic performance as measured by VO2max has been shown to reduce by 5 -15% in trained and active women using a triphasic OCP [95,96], however, research remains equivocal when considering the monophasic pill [72]. Anaerobic performance, high-intensity intermittent performance and strength appear to be largely unaffected by OCP, however, more well-controlled studies are required [72,93].…”
Section: 2)mentioning
confidence: 99%
“…Some studies have indicated that physiological fluctuations that occur throughout the menstrual cycle and/or as a result of OCP usage may affect physical performance [84,93,95]. One study has revealed that the use of the OCP (during the withdrawal phase) has been shown to elicit significantly lower reactive strength index scores during a drop jump.…”
Section: )mentioning
confidence: 99%
“…Interestingly, the investigators found no changes in endurance performance, heart rate, or ventilation to account for this effect. Casazza et al, reported similar findings in a small study in six "moderately active" women [19]. Participants were studied before and after four months of a triphasic oral contraceptive during the follicular and luteal phases.…”
Section: Introductionmentioning
confidence: 60%
“…Exogenous progesterone administration has also been associated with increased core body temperature [8]. Data also suggest that during the luteal phase (days [16][17][18][19][20][21][22][23], when estradiol and progesterone levels are elevated, lactate production is decreased in response to exercise [9]. Exogenous administration of progesterone has been linked to increases in ventilation and administration of combined oral contraceptives can decrease fasting blood glucose levels and increase serum triglycerides [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Most researche xamining the effects of menstrual cycle phase on exercise performance hasu sed inactive or moderately active women (Casazza et al, 2002;Oosthuyse &B osch, 2010;Smekel et al, 2007), and little has been done with highly trained athletes. Becausei ti sm ore important for highly trainedathletes to perform well in their sport than it is for recreational exercisers, it is crucial to understand howt he body responds to the fluctuations of hormones in the menstrual cycle in eliteathletes and howit can affect physiological responses to exercise.…”
mentioning
confidence: 99%